Chest CT diagnostic potential as a tool for early detection of suspected COVID-19 cases in pandemic peaks - Chervenkov, Lyubomir; Raycheva, Ralitsa; Rangelova, Vanya; Doykova, Katya (Folia Medica, 2023)
Introduction: The emergence of severe acute respiratory syndrome coronavirus disease (COVID19) in China at the end of 2019 caused a massive global outbreak that has become a major public health issue. Aim: Our aim was to investigate the diagnostic potential of chest CT in screening patients suspected of having COVID19 in highprevalence settings. Materials and methods: This is a reallife, prospective, observational study involving 260 patients. All patients received chest CT scan at the emergency department (ED) of Kaspela University Hospital, Plovdiv, Bulgaria and RTPCR testing for suspected COVID19 from March 27 to December 31, 2020. COVID19 likelihood was assessed by assigning each CT scan to a particular category of the COVID19 Reporting and Data System (CORADS). IBM SPSS v. 26 was used to process the data. Results: The maletofemale distribution ratio was 1.4:1 - 150 (57.7%) males vs. 110 (42.3%) females (p=0.014). The median age was 55 yrs (range 46-65 yrs). Discharged patients were 247 (95.0%), the rest died in the COVID19 intensive care unit. Males were 4.13 times more likely to be diagnosed with CORADS≥3 score than females. Increasing age was associated with an increased likelihood of being classified with higher CORADS scores. The ROC curves analysis demonstrated that CORADS ≥3 was the optimal cutoff for discriminating between a positive and negative PCR (Youden's index J=0.67), with an AUC of 0.825 (95% CI 0.720.93), sensitivity of 91.9% (95% CI 87.7%95.1%), specificity of 75.0% (95% CI 53.3%90.2%) and accuracy of 76.4% (95% CI 70.7%81.4%). Conclusions: The results of this study reveal that a CT examination can provide a quick and accurate diagnosis of patients with suspected COVID19 infection, whereas the PCR test is timeconsuming, and the delay in receiving results can be substantial when the incidence curve begins to grow rapidly.